Sosialisasi Mitigasi Bencana Terhadap Infrastruktur Jalan di Kawasan Rawan Bencana - Karyawan, I Dewa Made Alit (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Santong Village, Kayangan Sub-district, North Lombok Regency, is a disaster-prone area that can significantly affect road infrastructure and community activities. Several potential natural hazards in this area include landslides, floods, and earthquakes, with landslides being the most dominant, especially during the rainy season. To enhance community awareness of disaster mitigation, particularly regarding its impact on road infrastructure, a socialization program was conducted on July 19, 2025. The activity was attended by 25 participants from the local youth organization (Karang Taruna) and featured two speakers from the Regional Disaster Management Agency (BPBD) and University of Mataram. The topics presented covered the potential disasters in Santong, evacuation route mapping, and disaster mitigation strategies related to road infrastructure. Evaluation through pre-test and post-test showed a 20% increase in participants’ understanding. The success of this activity indicates that disaster mitigation education should be conducted continuously, especially since landslides remain the main threat to road infrastructure in Santong Village.